Religious Moderation and Local Tradition: A Case Study of Sedekah Desa in East Java, Indonesia - Faradila Ema Nur Azizah; Wildhan Ichza Maulana; Bakhruddin Fannani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study investigates how the Sedekah Desa ritual practiced in Kandangan Village, East Java, embodies key dimensions of religious moderation. Employing a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation of ritual activities. The findings reveal that the tradition promotes four central indicators of religious moderation: (1) tolerance (tasāmuh)—evident in the inclusive prayer practices involving different religious groups; (2) equality (musāwah)—reflected in the shared participation across all social strata during communal meals; (3) justice (iʿtidāl)—symbolized through the jolen procession representing the balance between devotion to God (ḥabl min Allāh) and social solidarity (ḥabl min al-nās); and (4) adaptability (taṭawwur wa ibtikār)—seen in the community’s creative integration of Islamic values with local cultural expressions. These findings suggest that the Sedekah Desa ritual functions as a dynamic socio-religious mechanism that fosters inclusivity, intergroup harmony, and cultural resilience in contemporary Indonesian society.